2022
DOI: 10.1101/2022.12.29.522270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polygenic prediction across populations is influenced by ancestry, genetic architecture, and methodology

Abstract: Polygenic risk scores built from multi-ancestry genome-wide association studies (GWAS, PRSmulti) have the potential to improve PRS accuracy and generalizability across populations. To provide the best practice to leverage the increasing diversity of genomic studies, we used large-scale simulated and empirical data to investigate how ancestry composition, trait-specific genetic architecture, and PRS methodology affect the performance of PRSmulti as compared to PRS constructed from single-ancestry GWAS (PRSsingl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Specifically, we found that the PRS scores were more predictive when the selection of the appropriate PRS model for each particular individual was ancestry specific, which necessarily requires ancestry estimation prior to PRS estimation. It should be noted that the top selected models for CAD [22][23], were generated with genome-wide summary statistics derived from transethnic studies, which agrees with studies demonstrating the increased PRS predictability in multi-ethnic samples [11]. Although our approach does not solve the transferability problem impacting PRSs, we provide an alternative strategy to identify those conditions and ancestries where PRSs could work efficiently.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Specifically, we found that the PRS scores were more predictive when the selection of the appropriate PRS model for each particular individual was ancestry specific, which necessarily requires ancestry estimation prior to PRS estimation. It should be noted that the top selected models for CAD [22][23], were generated with genome-wide summary statistics derived from transethnic studies, which agrees with studies demonstrating the increased PRS predictability in multi-ethnic samples [11]. Although our approach does not solve the transferability problem impacting PRSs, we provide an alternative strategy to identify those conditions and ancestries where PRSs could work efficiently.…”
Section: Discussionsupporting
confidence: 68%
“…. Conversely, PRS performances relative to Europeans improved when we specifically selected the optimal PRS for a given condition and a given population ancestry, reinforcing the idea that optimal PRS methods are trait and context specific [11].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our use of mCAIDE was determined by the lack of extensive lifestyle and social determinants of health data, precluding the use of more comprehensive dementia risk scores. Second, the predictive accuracy of PRS models is affected by the sample size ratio between the EUR and minor GWAS, betweenancestry genetic architecture differences (LD, MAF, genetic correlation, heritability, effect size), and LD reference panels 34 , 35 . As such, the choice of PRS model to use for portability across populations will differ between traits.…”
Section: Discussionmentioning
confidence: 99%
“…These methods directly model LD patterns through haplotype information and should therefore be able to tag unobserved causal SNPs, which are poorly captured by an SNP array or imputed genotype data, due to the unobserved SNPs likely being in identity-by-state for long haplotypes being in identity-by-state [41]. Multiple approaches including local ancestry tracts inferred from haplotypes have also been developed to estimate SNP heritability [65] and construct reference-based PRS estimators [57].…”
Section: Introductionmentioning
confidence: 99%